2017
DOI: 10.3390/nu9020177
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet and Its Correlates among Adolescents in Non-Mediterranean European Countries: A Population-Based Study

Abstract: Little is known about the factors which might influence the adherence to a Mediterranean diet in non-Mediterranean European countries. Thus, the main purpose of this study was to determine the associations between socioeconomic, psychological, and physical factors on a Mediterranean diet. In this cross-sectional study, participants were 14–18-year-old adolescents (N = 3071) from two non-Mediterranean countries: Lithuania (N = 1863) and Serbia (N = 1208). The dependent variable was Mediterranean diet, and was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 54 publications
2
38
1
2
Order By: Relevance
“…Although the feasibility and acceptability of the MD has been explored in older people and those in middle age [ 37 , 38 , 49 , 50 ], to date there has been no research that has investigated the feasibility of promoting an MD to women of childbearing age, with only evidence from cross-sectional studies in adolescent girls and women in early adulthood suggesting poor adherence to diet patterns similar to the MD [ 51 , 52 ]. Promoting a healthy diet in women of childbearing age can have a significant impact on both maternal and child health; however, the present study demonstrates that whilst an MD may be generally well received, adherence would require several obstacles to be overcome.…”
Section: Discussionmentioning
confidence: 99%
“…Although the feasibility and acceptability of the MD has been explored in older people and those in middle age [ 37 , 38 , 49 , 50 ], to date there has been no research that has investigated the feasibility of promoting an MD to women of childbearing age, with only evidence from cross-sectional studies in adolescent girls and women in early adulthood suggesting poor adherence to diet patterns similar to the MD [ 51 , 52 ]. Promoting a healthy diet in women of childbearing age can have a significant impact on both maternal and child health; however, the present study demonstrates that whilst an MD may be generally well received, adherence would require several obstacles to be overcome.…”
Section: Discussionmentioning
confidence: 99%
“…physical fitness among adolescents have deteriorated in the past 20 years, and the indicators of cardiorespiratory fitness have decreased by nearly 50% during this period [3]. Only 13-14% of high school students comply with recommendations for healthy nutrition [4,5], 11% of young people consume alcohol [6]. Moreover, 22% experience psychological distress [7].…”
mentioning
confidence: 99%
“…Moreover, the high consumption of products rich with minerals and plant foods rich with antioxidants contribute to the health of vascular system and reduction of high arterial blood pressure [ 43 ]. Most recently, a study conducted on a large sample of European adolescents showed, that participants, who were overweight and obese had increased odds of reporting low MD [ 44 ]. We also found that MD is inversely related with heart rate, which is consistent with some previous findings [ 45 ].…”
Section: Discussionmentioning
confidence: 99%